Quantitative evaluation of the joint effect of uncertain parameters in CO2 storage in the Sleipner project, using data-driven models. (December 2020) - Ahmadinia, Masoud; Shariatipour, Seyed M.; Andersen, Odd; Nobakht, Behzad
Highlights: Joint effect of uncertain parameters affecting the overall CO2 migration and trapping in the model is studied. To make the study computationally feasible the simulations are performed using the VE approach. Uncertain parameters include porosity and permeability heterogeneity, reservoir temperature, pressure and caprock elevation. Caprock elevation was shown to be the most important parameter in controlling the plume migration. Abstract: Several researchers have studied the Sleipner model to understand the inherent flow physics better, to find a satisfactory match of the CO2 plume migration. Various sources of uncertainty in the geological model and the fluid have been investigated. Most of the work undertaken on the Sleipner model employed the one factor at a time (OFAT) method and analysed the impact of uncertain parameters on plume match individually. In this study, we have investigated the impact of some of the most cited sources of uncertainties including porosity, permeability, caprock elevation, reservoir temperature, reservoir pressure and injection rate on CO2 plume migration and structural tapping in the Sleipner. We tried to fully span the uncertainty space on Sleipner 2019 Benchmark (Layer 9) using a vertical-equilibrium based simulator. To the best of our knowledge, this is the first time that a study has focused on the joint effect of six uncertain parameters using data-driven models. This work would raise our scientific understanding of the complexity of the impact of the reservoir uncertainty on CO2 plume migration in a real field model. The caprock elevation was shown to be the most important parameter in controlling the plume migration (overall importance of 26 %) followed by injection rate (24 %), temperature (22 %), heterogeneity in permeability (13 %), pressure (9 %) and porosity (6 %).